Efficacy of Muscle Energy Technique alone and in combination with Interferential Therapy for the Treatment of Non-specific Low Back Pain: Treatment of Non-specific Low Back Pain - Zubair, Ali; Shakoor, Imama; Hassan, Muhammad Saad; Tahreem, Shumaila; Iqbal, Mehwish; Haq, Kiran; Salman, Muhammad (Pakistan Journal of Health Sciences, 2023)
Non-specific back pain is one of the prevalent musculoskeletal disorders in general population worldwide and also a major contributor of days lost from the work. It is considered one of the major causes of financial burden on the healthcare. Objective: To compare the effectiveness of muscle energy technique alone and in combination with interferential therapy in the management of non-specific back pain. Methods: After getting the review ethical committee approval from The Neurocounsel Clinics, current RCT was initiated from 21 May, 2023 to 20 September 2023 and registered at ClinicalTrails.gov under NCT06098053. Sample size was calculated by Epitool which came 30. Simple random sampling technique was used to randomize participants into two equal groups. Group A was given muscle energy technique and group B was given muscle energy technique plus interferential therapy. 2 sessions/week for 4 & half weeks. Evaluation was done at pain numeric scale & EQ-5D-5L (QoL). Pre and post-test analysis was done by use of SPSS version 21 and level of significance was kept p<0.05. Results: The mean age in group A was 31.40±10.91 whereas in group B it was 26.93±11.69. Mann Whitney U test showed significant difference (p<0.05) between groups on the basis of PNS and insignificant difference (p>0.05) between groups on the basis of QoL. Conclusions: It was concluded from the results of this study that MET and IFT are more effective in alleviating patient’s pain but are equally effective in improving quality of life in patients suffering from non-specific back pain.